Aphasic Dystextia as Presenting Feature of Ischemic Stroke in a Pediatric Patient - Arpita Lakhotia; Alok Sachdeva; Supriya Mahajan; Nancy Bass (Case Reports in Neurological Medicine)
Aphasia is an important presenting symptom of acute stroke. With increasing reliance on electronic communication, incoherent texting or “dystextia,” which is a subset of aphasia that is reflected in text messages, can be a useful tool for symptom recognition and analysis. It can be a red flag for the family and therefore can help in early identification of an acute neurological deficit. It is also useful for providers to reliably analyze the deficit as well as establish a timeline of evolution of symptoms. There have been case reports where dystextia has been the presenting feature of stroke or complicated migraine and in one case of meningioma. We present the case of a teenage patient that in our knowledge is the youngest reported case of dystextia, whose aphasia recorded in a text message assisted with stroke localization. This also adds to the literature of dystextia which so far has only seven other cases reported.